Progress in reducing ICRF-specific impurity release in ASDEX upgrade and JET. (August 2017) - Bobkov, V.; Aguiam, D.; Baruzzo, M.; Borodin, D.; Borodkina, I.; Brezinsek, S.; Coffey, I.; Colas, L.; Czarnecka, A.; Delabie, E.; Dumortier, P.; Durodie, F.; et al.
Highlights: ICRF antenna design and tuning in ASDEX Upgrade has a major influence on W release. 3-strap antenna with W-coated limiters has reduced RF image currents and W sputtering. ITER-like antenna in JET-ILW produces less W than A2 antenna. Role of SOL impurity transport modifications by convective cells in JET-ILW is small. Abstract: Use of new 3-strap ICRF antennas with all-tungsten (W) limiters in ASDEX Upgrade results in a reduction of the W sources at the antenna limiters and of the W content in the confined plasma by at least a factor of 2 compared to the W-limiter 2-strap antennas used in the past. The reduction is observed with a broad range of plasma shapes. In multiple locations of antenna frame, the limiter W source has a minimum when RF image currents are decreased by cancellation of the RF current contributions of the central and the outer straps. In JET with ITER-like wall, ITER-like antenna produces about 20% less of main chamber radiation and of W content compared to the old A2 antennas. However the effect of the A2 antennas on W content is scattered depending on which antennas are powered. Experiments in JET with trace nitrogen (N2 ) injection show that a presence of active ICRF antenna close to the midplane injection valve has little effect on the core N content, both in dipole and in -90° phasing. This indicates that the effect of ICRF on impurity transport across the scape-off-layer is small in JET compared to the dominant effect on impurity sources leading to increased impurity levels during ICRF operation.